IPads and interaction: a materials perspective on collaborative discourse in secondary Spanish immersion. Issue 1 (3rd April 2021) - Mathieu, Corinne S.
ABSTRACT: As digital technologies proliferate throughout classrooms in the United States, iPads and other mobile tablets have been heralded as tools for enhanced peer collaboration. However, little research has examined exactly how students interact with and around iPads during collaborative learning tasks. This study employs multimodal interaction analysis to investigate how secondary Spanish immersion students leveraged the physicality of the iPads as multimodal affordances when completing a world history literacy-based task in a target language. In particular, I consider how the focal students employed touch-based communicative modes to complete higher-level actions, and the potential relationship between these modes and target language development. Findings have implications for materials use research in language teaching/learning classrooms as well as progressing our understanding of the impact of iPads on classroom discourse.